The relationship between employees' perception towards performance appraisal system and work performance in a telecommunication company in Kuching, Sarawak - Jimali, Anak Sunang. (2001)
The purpose of this study is to look into the relationship between the employeesʼ perception towards the performance appraisal system in Celcom Sdn. Bhd. related to their perception towards work performance in the organization. Two factors between the dependent and independent variable were investigated to identify the differences and its effect towards the organizationʼs achievement, goals, and mission.